2012
DOI: 10.1111/j.1445-5994.2011.02498.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple clinical score is associated with mortality and length of stay of acute general medical admissions to an Australian hospital

Abstract: The SCS can predict significant outcomes for general medical admissions in an Australian hospital despite obvious differences to the hospital of its derivation. A wider study of Australasian hospitals and the performance of the SCS as a predictor of general medical admission outcomes is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…While generated to predict 30‐day mortality risk, it may prove to be a valuable tool for assessing and comparing the quality of clinical care between different units or different hospitals. Our comparison of a recent Royal Adelaide Hospital study with three other published studies on the SCS show similar trends across the four sites for a variety of outcomes despite the GM units being of differing sizes (36–120 beds), hospitals of differing sizes (180–980 beds), catchments of differing sizes (60 000–1 200 000) containing mostly rural patients or mostly urban (Table ). We suggest that the SCS has the potential to be used, together with RSI, as a tool to compare performance of different sites because it controls for some crucial patient factors beyond those used to calculate the RSI.…”
Section: Proposalsupporting
confidence: 62%
“…While generated to predict 30‐day mortality risk, it may prove to be a valuable tool for assessing and comparing the quality of clinical care between different units or different hospitals. Our comparison of a recent Royal Adelaide Hospital study with three other published studies on the SCS show similar trends across the four sites for a variety of outcomes despite the GM units being of differing sizes (36–120 beds), hospitals of differing sizes (180–980 beds), catchments of differing sizes (60 000–1 200 000) containing mostly rural patients or mostly urban (Table ). We suggest that the SCS has the potential to be used, together with RSI, as a tool to compare performance of different sites because it controls for some crucial patient factors beyond those used to calculate the RSI.…”
Section: Proposalsupporting
confidence: 62%
“…SCS has been validated in various settings, but only a few independent studies have been done [4], [5], [6]. These all point in the direction that SCS is a valid tool to use in the MAU.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that SCS can be used in MAUs to predict LOS, and as a guide in finding patients at risk for intensive critical care. [4] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Simple Clinical Score (SCS) is a reliable instrument that objectively assesses and measures severity of illness that has been independently validated in several different clinical settings. [1][2][3][4] Approximately 12% of patients increase their SCS 24 hours after admission to hospital. We recently reported that low risk patients were just as likely to increase their SCS as high risk patients, and that an increased SCS was associated with a 5 fold increase in in-hospital mortality compared to patients with an unchanged SCS and a 20 fold increase in mortality compared to those with a decreased SCS.…”
Section: Introductionmentioning
confidence: 99%